A Survey of Tools and Techniques for Web Attack Detection - Dau, Hoang Xuan; Trang, Ninh Thi Thu; Hung, Nguyen Trong (Journal of Science and Technology on Information security, 2022)
Abstract— Web attacks include types of attacks to websites and web applications to steal sensitive information, to possibly disrupt web-based service systems and even to take control of the web systems. In order to defend against web attacks, a number of tools and techniques have been developed and deployed in practice for monitoring, detecting and preventing web attacks to protect websites, web applications and web users. It is necessary to survey and evaluate existing tools and techniques for monitoring and detecting web attacks because this information can be used for the selection of suitable tools and techniques for monitoring and detecting web attacks for specific websites and web applications. In the first half, the paper surveys some typical tools and techniques for monitoring and detecting web attacks, which have been proposed and applied in practice. The paper’s later half presents the experiment and efficiency evaluation of a web attack detection model based on machine learning. Experimental results show that the machine learning based model for web attack detection produces a high detection accuracy of 99.57% and the model has the potential for practical deployment.